Vulvoscopía and directed biopsy in vulvar infection by human papilloma virus - Herrera, Gustavo (2015)
Human papilloma virus (HPY9 vulvar infection is the most frequent pathology of the external genitalia. Because the infection is often subclinical, vulvoscopy and directed biopsy are needed for a correct diagnosis. During one year, 316 women were studied by colposcopy and biopsy and at least one vulvar pathology was diagnosed in 86 cases (27%). HPV vulvar infection was the most prevalent disorder (68%). Active sexual women were more affected, nearly half of the cases were subclinical and the diagnosis was done only by colposcopy and biopsy. The fourchet and the inner face of the labia minora appear as frequent localizations. In 20% of cases, HPV infection involved also cervix and vagina and different 9 cervical neoplasia were seen in 45% of infected patients. Oral contraceptives, IUD and bilateral salpingotomy appear to be risk factors to develope the vulvar infection.